Harmonization of Waqf Money (Cash Waqf) at the University of Bung Hatta - Desmal Fajri; Sanidjar Pebrihariati R; Yofiza Media (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Bung Hatta university has hundreds of lecturers and education personnel as well as thousands of students that can be used as wakif (the one who donated) waqf money. The results of the waqf money are used the scholarship as one of the efforts to increase the number of students and helps its operational costs to the future. This research using qualitative research methods. The source of the research data consists of primary data and secondary data. Data collection techniques conducted interviews by the respondents. And this study was analyzed by descriptive qualitative. The results of the research that the University of Bung Hatta has the potential developed waqf money (cash waqf) because it has the lecturers and education personnel as much as 446 people (99,33 %) are muslims also get a salary and fixed allowances each month of the Education Foundation of Bung Hatta, the student and his parents are muslims as much as 7.525 people (98,14%). In addition, the support of the Chairman of the Education Foundation of Bung Hatta to realize the potential of the above with a policy.